Karya- Karya Aqidah Islam: Satu Tinjauan Ringkas Terhadap Penulisannya Sepanjang Zaman - Mat, Johari (Jurnal Usuluddin, 1998)
This articles attempts to focused on Islamic written texts that has been produced by Islamic scholars from time to time.